Sérieuse, audacieuse, bienheureuse... Généreuses! Rencontre avec Isabelle Panneton, Marie Pelletier et Ana Sokolovic - Davoine, Françoise (Circuit : musiques contemporaines, 1999)
In this exchange with three women composers, Françoise Davoine draws a portrait of their risks, anguish and preoccupations. The speaking-style of the text has been preserved here, giving freshness to the statements as each woman talks about her situation, and the creative process, etc.